MENINGKATKAN KESADARAN LITERASI MEDIA PADA ANAK DI DESA PAJAGAN KECAMATAN SAJIRA KABUPATEN LEBAK BANTEN (Lembaran Masyarakat: Jurnal Pengembangan Masyarakat Islam, 2023)
The literacy level of the Indonesian people is quite low. This is based on the Indonesian Digital Literacy Index organized by the Ministry of Communication and Informatics and Katadata Insight Center (KIC) in 2021, Indonesia's digital literacy index is at 3.49 and Digital Safety gets an index score of 3.12. In this low literacy culture, it is hoped that it will not have bad implications for children. Because according to data from the Ministry of Communication and Information, generation Z and Y internet access lasts more than 6 hours. These data show that digital media exposure in children is much greater and of higher intensity. In the development of literacy in several major cities in Indonesia, Banten occupies the 9th position for Literacy but in terms of the fulfillment of infrastructure, it is ranked 5th at the bottom. Children as the next generation to get appropriate exposure and awareness of the importance of literacy. In this study FGD and interview techniques were used as well as observation in collecting data packaged in descriptive qualitative data. From this data it is known that the urgency of literacy in children cannot be carried out without support from various parties. Literacy suggestions must be raised at the nearest scale to provide significant awareness. Data shows that parents are the main center of children's activities and a trusted source for children, besides that friends and education are the main supporting parts. However, the existence of the media is an important variable in children's awareness of literacy.